An Exegetical Study of 1 Timothy 6:3–12 with Special Reference to Its Implications for the Prosperity Gospel - Dlamini, Sifoso T. (South African Theological Seminary, 2018)
The prosperity gospel (PG) is a widespread theology among certain denominations of the Christian church. The essence of this theology is the teaching that Christians have a right to wealth and health through positive confession and is based on a selection of texts in the Bible. The prosperity gospel, on closer examination, is the result of a very particular view of the Bible. The Bible is primarily seen as a faith contract between God and believers. Along this way, God is manipulated by the believer to fulfill his or her wants or desires. Most have come to believe that whatever they desire from God, they must simply speak (claim) it by faith. Positive confession means, therefore, that believers are speaking in faith what they believe God has already promised to them. At the heart of the prosperity teaching lies the conviction that no Christian is destined to suffer and live in poverty on this earth The prosperity gospel has been examined and analysed in the light of what the Bible teaches about wealth and health. The study is limited to an exegetical study of 1 Timothy 6:3-12. The results as well as the practical implications and warnings are discussed. It concludes with a summary of the prosperity gospel, detailing its faithfulness or infidelity to the biblical text. Recommendations are suggested that, taken together, are considered to be an appropriate response to advocates of that gospel.
free